2022
DOI: 10.1371/journal.pone.0267375
|View full text |Cite
|
Sign up to set email alerts
|

Feedback of individual genetic and genomics research results: A qualitative study involving grassroots communities in Uganda

Abstract: Background Genetics and genomics research (GGR) is associated with several challenges including, but not limited to, methods and implications of sharing research findings with participants and their family members, issues of confidentiality, and ownership of data obtained from samples. Additionally, GGR holds significant potential risk for social and psychological harms. Considerable research has been conducted globally, and has advanced the debate on return of genetic and genomics testing results. However, su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 43 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…The issue of GGR affordability of genetic testing has also been raised in a related study involving grassroots communities in Uganda that proposed the use of meaningful and beneficial community engagement to address the gaps and facilitate poststudy access. 19 The fears concerning the cost of genetic testing is worsened by the fact that African populations retain more genetic diversity yet are tremendously under-represented in genetic studies. Limited genetic data and testing services on the continent as a consequence of global health inequity remains a social justice challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of GGR affordability of genetic testing has also been raised in a related study involving grassroots communities in Uganda that proposed the use of meaningful and beneficial community engagement to address the gaps and facilitate poststudy access. 19 The fears concerning the cost of genetic testing is worsened by the fact that African populations retain more genetic diversity yet are tremendously under-represented in genetic studies. Limited genetic data and testing services on the continent as a consequence of global health inequity remains a social justice challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The FGDs were conducted using a guide adopted from related work. 19 Respondents were assessed about their perspectives in a hypothetical GGR setting. Initially, participants were asked general questions on awareness and knowledge about genetics, this was followed by an explanation/ educational session on genetics, genes, DNA, genome, genetic testing and feedback of results lasting about 30 min.…”
Section: Data Collectionmentioning
confidence: 99%
“…They can be facilitated by use of relevant life scenarios and other educative materials, such as visual aids to enhance participants’ comprehension of pharmacogenomics research information. Similar studies have also highlighted the need to use such materials to promote participants’ complete understanding of genomics and genetics studies (Ochieng et al, 2022; Wilczewski, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, studies from sub-Saharan Africa have reported inadequate, unclear, or an absence of national guidelines for the returning of genomics research results, yet the ethical, legal, and social implications of these results do not only affect participants but may also affect family members and research communities (Chanda-Kapata et al, 2015; de Vries et al, 2017; Staunton and de Vries, 2020). Researchers in sub-Saharan Africa have reported several ethical considerations for the returning of individual genomic and genetics results, including the need for community engagement, genetics counselling services and determining appropriate methods of communicating genetics results to participants (Matimba et al, 2022; Ochieng et al, 2022). However, there is limited literature on how individual results from pharmacogenomics research should be safely returned to people living HIV, a chronic disease that is still associated with many ethical and social issues.…”
Section: Introductionmentioning
confidence: 99%
“…These guidelines emphasize that communities are not homogeneous, so researchers ought to employ creative approaches that minimize the potential risks to participants and research communities when communicating pharmacogenomic and genomic information. It is important to note that individual pharmacogenomic and genomic research results may present findings with ethical, legal and social implications that may not only affect research participants but also extend to families and research communities [32]. Therefore, inappropriate approaches of communicating pharmacogenomic research results at community and individual levels might raise concerns such as loss of privacy and breach of confidentiality, which may stigmatize research participants and their family members.…”
Section: Introductionmentioning
confidence: 99%